If f ( x + y , x − y ) = x y , the find the arithmetic mean of f ( x , y ) and f ( y , x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The above functional equation can be written as:
f ( x + y , x − y ) = x y = 4 1 ⋅ [ ( x 2 + 2 x y + y 2 ) − ( x 2 − 2 x y + y 2 ) ] = 4 1 ⋅ [ ( x + y ) 2 − ( x − y ) 2 ] ,
Hence, our required function is f ( x , y ) = 4 x 2 − y 2 . The arithmetic mean of f ( x , y ) and f ( y , x ) computes to:
M = 2 1 ⋅ [ 4 x 2 − y 2 + 4 y 2 − x 2 ] = 8 1 ⋅ 0 = 0 .
Problem Loading...
Note Loading...
Set Loading...
Let x = a + b and y = a - b
Then f( x , y ) = f ( a + b , a - b ) = a * b
Then f ( y , x ) = f (a -b , a + b) = f ( a + (-b) , a - (- b) ) = a * (- b) = - (a*b)
arithmetic mean = sum divided by 2
a b + (- a b) = 0
0 / 2 = 0